Analysis Of Service Quality On Customer Satisfaction In The Safa Shoecare Shoe Cleaning Business - Naswa, Indi; Satria Aranda, Rafli; Kisawati Zaini, Oktori (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
In the current era of globalization where the human lifestyle is increasingly modern, changes in the increasingly modern human lifestyle have also changed various aspects of supporting human life. This research is motivated by the Safa Shoecare Shoe Washing Business which is experiencing problems with service quality that makes customers less satisfied with the quality of service provided. This is thought to have occurred because the company has not been optimal in providing maximum service to consumers. This study aims to determine the analysis of service quality on customer satisfaction at Safa Shoecare by involving 90 people who became respondents in data collection processed using SPSS Version 28. Based on the calculation of the Slovin formula, data collection was carried out through questionnaires and interviews and data processing was carried out by tabulation and scoring for data analysis methods using descriptive analysis, Important Perfomance Analylyze method. Based on the results, the overall average value of the 5 indicators described in 20 statement items is 87.7%, then for the highest average per indicator lies in the reliability indicator with a percentage of 88.6%, while for the lowest average per indicator there is an indicator of physical evidence with a percentage of 82.6%. Based on the calculation of the level of conformity, the result is 102.87% which indicates that the level of conformity between performance and expectations is above 100%, this shows that the quality of service provided by Safa Shoecare is in accordance with consumer expectations. Based on the results of Importance Performace Analysis or IPA, the indicator of physical evidence (Tangible) with the attribute The decoration of the place is made attractive and the completeness of Safa shoecare facilities. Responsiveness with attributes Safa Shoecare employees are quick and responsive in responding to customer complaints, empathy (Emphaty) with attributes Safa Shoecare employees ensure the completeness of consumer orders, Assurance with attributes Safa Shoecare employees' ability to build trust with consumers. This attribute is in quadrant A (top priority), this certainly needs to be a concern for the owner of Safa Shoecare to evaluate and improve service quality in order to be able to provide the satisfaction expected by consumers.